Elucidating the relationship between burnout and sleep disturbances among firefighters: a network analysis - Bin Liu; Lin Liu; Lei Ren; Zhujing Ma; Mingxuan Zou; Yu Li; Mengze Li; Yuting Feng; Zhongying Wu; Tifei Yuan; Yinchuan Jin; Qun Yang (BMC Public Health)
Abstract Background There exists an intricate relationship between burnout and sleep disturbances, especially among firefighters. Network analysis offers novel perspectives for understanding the interactions of psychopathological variables. This study aims to elucidate the relationship between burnout and sleep disturbances among firefighters through network analysis. Methods A total of 1,486 Chinese firefighters were included in this study. The Maslach Burnout Inventory-General Survey (MBI-GS) (Chinese version) and the Pittsburgh Sleep Quality Index (PSQI) were used to assess burnout and sleep disturbances among firefighters, respectively. Two network construction methodologies, the regularized partial correlation network (RPCN) and the directed acyclic graph (DAG), were employed to perform network analysis. Results Within the RPCN, “Subjective sleep quality” emerged as the central domain of firefighters’ burnout and sleep disturbances, as well as “Emotional exhaustion” and “Daytime dysfunction” were influential bridge domains connecting the two. From the results pertaining to the DAG, “Subjective sleep quality” was the activation domain that triggered other burnout and sleep disturbance domains, with sleep disturbances serving as the potential cause of burnout. Conclusions Our findings offer some enlightenment into further understanding the relationship between burnout and sleep disturbances in firefighters. Furthermore, the aforementioned central, bridge, and activation domains may be potential targets for prevention and intervention.